FROM TRADITIONAL TO DIGITAL: THE EVOLUTION OF AUDITOR COMPETENCIES AND AUDIT PRACTICES - Nadia Husnaningtyas (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This literature review investigates the evolving landscape of audit methodologies in response to digitalization, specifically analyzing the shifting skill sets auditors must possess. Conducted as a Systematic Literature Review (SLR), the research establishes a core model interlinking the digital auditor, contemporary audit procedures, and technology-enabled audits as the cornerstone of modern practice. The analysis reveals that for the audit profession to maintain its credibility and effectiveness, practitioners must cultivate a blend of advanced technical skills, digital fluency, and a commitment to lifelong learning. The study subsequently constructs a paradigm for implementing innovation in auditing that is both ethically grounded and operationally robust. It concludes by outlining the practical imperative for auditors to evolve their roles, emphasizing moral responsibility and adaptive expertise amidst technological change. For further academic inquiry, this paper suggests exploring the moral dimensions of automated auditing and creating customized innovative models for various industrial settings.